Distance between ROV and sea ice from ROV survey PS122/5_59-369 on 2020-08-29, survey 1 - Anhaus, Philipp; Katlein, Christian; Matero, Ilkka; Nicolaus, Marcel; Arndt, Stefanie; Krampe, Daniela; Lange, Benjamin Allen; Regnery, Julia; Rohde, Jan; Schiller, Martin (In: Anhaus, P et al. (2022): Single-beam sea-ice draft from remotely operated vehicle (ROV) surveys during the MOSAiC expedition 2019/20 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.951647, 2022)
The distance between a remotely operated vehicle (ROV) and the sea-ice underside was measured by a single-beam upward-looking acoustic sonar altimeter (Tritech PA500) attached to the ROV during the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition between November 2019 and September 2020. Sea-ice draft was derived by subtracting the distance to the sea-ice underside from the ROV depth, uncorrected for ROV attitude (pitch, roll). An offset between the depth reference (ROV bumper bars) and the altimeter of 0.105 m is accounted for in the presented data.
Keywords: BEAST; MOSAiC expedition; Remotely operated vehicle (ROV); Sea ice; Sea-ice draft